(untitled) (Medical Forum Monthly, 2020)
Objective: To Determine the frequency of postoperative Ligasure complications in 3rd and 4th degree hemorrhoids. Study Design: Place and Duration of Study: This study was conducted at the Department of Surgery Unit-II, Peoples University of Medical and Health Sciences, Nawabshah, LUMHS Jamshoro and Suleman Roshan Medical College Hospital, Tandoadam, from February 2019 to January 2020. Materials and Methods: Inclusion criteria were patients above 16 years age with diagnosed 3rd and 4th degree hemorrhoid. Patients under 16 years, anticoagulant therapy, previous anal surgery and immunosuppressed patients were excluded from the study. Take a detail history from all patients regarding bleeding per rectum or something coming out during defecation. These patients were admitted to the Surgery ward early morning of the procedure and discharged the following day, except when they had to stay longer due to postoperative complications. The data was collected on a structured proforma, analyzed statistically and the results were tabulated. Results: During study period 144 cases were hemorrhoid, comprising 118 (82%) male and 26 (18%) female. Mean age of 29.3±3.5 years. Majority of patients were observed in 3rd and 4th decade 50 (34.72) and 55 (38.19) respectively. The clinical examination of 93 (64.58%) patients were 3rd degree hemorrhoids, followed by 4th degree hemorrhoids in 51(35.41%). The postoperative complications were observed, in which the most frequent one was the pain 36 (25%) cases, infection in 6 (4.16%) cases, anal spasm in 3(2.08%) cases and recurrence in 2 (1.38%) cases. Conclusion: We conclude that LigaSure hemorrhoidectomy is a suture less, less intra-operative blood loss, less required post-operative pain management and higher patient satisfaction.